Gender and Identity Subversion in Oli London's Plastic is Fantastic - Yasmine Anabel Panjaitan; Asyifa Yuditya (Universitas Airlangga, 2022)
The release of Oli London's Plastic Is Fantastic (2021), which talks about his fantasy of plastic surgery, has been extensively criticized. One of the reasons is that his music video was released during Pride Month, a month when the LGBTQ community advocates for their rights for gender equality, followed by other videos and tweets declaring his post-surgery transition to